Understanding Physiotherapists' Roles in Ontario Primary Health Care Teams - Dufour, Sinéad Patricia (University of Toronto Press Incorporated, 2014)
Purpose: To understand physiotherapists' roles and how they are enacted within Ontario primary health care (PHC) teams. Methods: Following a pragmatic grounded theory approach, 12 physiotherapists practising within Ontario PHC teams participated in 18 semi-structured in-depth in-person interviews. All interviews were audiotaped and transcribed verbatim, then entered into NVIVO-8. Coding followed three progressive analytic stages and was iterative in nature, guided by grounded theory. An explanatory scheme was developed. Results: Physiotherapists negotiate their place within the PHC teams through five interrelated roles: (1) manager; (2) evaluator; (3) collaborator; (4) educator; and (5) advocate. These five roles are influenced by three contextual layers: (1) inter-professional team; (2) community and population served; and (3) organizational structure and funding. Canada's PHC mandate (access, teams, information, and healthy living) frame the contexts that influence role enactment. Conclusions: To fulfill the PHC mandate, physiotherapists carry out multiple roles that are based on a broad holistic perspective of health, within the context of a collaborative inter-professional team and the community, through an evidenced-informed approach to care. There appear to be multiple ways of successfully integrating physiotherapists within PHC teams, provided that role enactment is context sensitive and congruent with the mandate of PHC.